L'efficacité de l'aide: Quelles évolutions de la littérature depuis deux décennies? - Lisa Chauvet; Marin Ferry (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– In the perspective of the Sustainable Development Goals and in the light of the Summit for a new global financial pact organized next June at the initiative of the French presidency, the question of the effectiveness of aid comes back more than ever to the front of the stage. The increase in the financial needs necessary for economic and social development in a context of growing climate threats and severe budgetary constraints in the countries of the North invites political decision-makers to ensure that each dollar, euro, or yuan spent impacts its recipient. If the scientific community has, since independence and until the end of the 2000s, tried to fuel the debates around the effectiveness of aid, it is clear that the conclusions are still fragile. Nevertheless, over the past twenty years and based on this mixed experience, science has adapted and renewed itself in order to overcome the methodological obstacles of past studies and bring a new perspective to these questions. What did she add to this supposedly endless debate? This article tries to answer it by dissecting the recent contributions of the literature on aid effectiveness.
Keywords: 330